The Wright brothers [large type] - McCullough, David G. (Thorndike Press large print popular and narrative nonfiction, 2015)
"As he did so brilliantly in THE GREAT BRIDGE and THE PATH BETWEEN THE SEAS, David McCullough once again tells a dramatic story of people and technology, this time about the courageous brothers who taught the world how to fly, Wilbur and Orville Wright"--Provided by publisher.